Exploration of Binary Oppositions in Nizami's Romantic Couplet Poems in Lyrical Literature - Sarhaddi, Fatemeh (2020)
Nezami’s romantic poems have brought about huge evolutions and changes in Iran’s literary space and this issue can be well discerned in the literary works authored after him. The literature of the world incorporates a large part of the human emotions, affections and thoughts influencing all the aspects of social and individual life. Epical, resistance, lyrical, theosophical and other types of literature all point to the large systems of texts each of which embrace truths of the world in a subject-specific manner. The present study explores the binary oppositions in the stories of Laili and Majnoun and Khosrow and Shirin. Interesting results can be obtained in a comparison of the two romantic poetical sets of “Khosrow and Shirin” and “Laili and Majnoun” including the idea that these two poetical sets reflect different cultures and issues. Khosrow and Shirin introduces the pre-Islam Iran’s status along with the customs and traditions of Sassanid kings and an open and well-calculated culture and Laili and Majnoun introduces the tribal life along with an image of the rigid customs and traditions as well as the closed culture of primitive Arabs. Love is earthly and virtual in Khosrow and Shirin and it transcends beyond the tangible world in Laili and Majnoun and seems to be more theosophical. The love of “Majnoun and Farhad” and “Laili and Shirin” and their death are very similar to one another and comparable. In Khosrow and Shirin, Shirin’s face overlooks the entire story and the outstanding role of Majnoun is clearly evident in the story of Laili and Majnoun